Integrating Zero Trust Architecture with Blockchain Technology to Maintain Data Security in the Cloud - T. Irfan Fajri; Handry Eldo; Cut Susan Octiva; Dikky Suryadi; Muhammad Lukman Hakim (International Journal Software Engineering and Computer Science (IJSECS), 2025)
Data security concerns have increasingly become a challenge to cloud computing services due to rising incidents of cyberattacks, identity theft, and data manipulation. The perimeter-based security model is ineffective because of vulnerabilities in authentication and access control, thus necessitating an adaptive layered approach. This paper presents attempts to merge Zero Trust Architecture (ZTA) with Blockchain technology as one possible way to ensure confidentiality, integrity, and availability of data in cloud environments. Research methodology comprises a detailed review of related literature, system architecture analysis, and simulation of the conceptual merger using encryption protocols and smart contracts. Results revealed that ZTA significantly reduces the opportunities for unauthorized access through multi-layered verification and least privilege principles while Blockchain provides a decentralized transparent immutable method for recording transactions on data. The hybrid will enhance security substantially against breaches from external attackers and insiders with an already established verifiable audit trail. This paper concludes that such a merger could create a stronger model—one that is more measurable—and sustainable for securing today's cloud infrastructure.